Canine Platelet-Rich Plasma Systems: A Prospective Analysis - Carr, Brittany Jean; Canapp, Sherman O.; Mason, David R.; Cox, Catherine; Hess, Theresa (Frontiers in Veterinary Science, 2016)
Objective: To quantitate key parameters of the platelet rich plasma (PRP) product from five commercial canine PRP systems in healthy, adult canines. Materials and Methods: A prospective study was performed from January 2013 to April 2014. Five commercial systems were analyzed using ten healthy dogs per system.a-e Blood was obtained according to the manufacturer’s protocol for each system. The mean baseline whole blood platelet, RBC, WBC, neutrophil, monocyte, and lymphocyte concentrations were determined for each PRP system. All blood samples were processed according to the manufacturer’s protocols. The mean PRP product platelet, RBC, WBC, neutrophil, monocyte, and lymphocyte concentrations were determined for each PRP system. These values were then compared to the mean baseline values. Comparisons of mean whole blood and mean PRP product parameters were calculated using a paired t-test with significance established at p = 0.05.g Results: Platelet concentration was significantly increased for System 1 (p=0.0088) and System 3 (p<0.0001), and was significantly decreased for System 2 (p<0.0001). All five systems significantly decreased the red blood cell concentration (p<0.0001 for each system comparison). Neutrophil concentration was significantly decreased for System 2, System 3, and System 4 (p<0.0001 for each system comparison). Neutrophil concentration was significantly increased for System 5 (p=0.0089). Clinical Relevance: The systems with the highest platelet yield were System 1 and System 3. System 3 increased platelet concentration while significantly reducing the RBC and neutrophil concentrations. Further study is indicated to assess the efficacy of PRP therapy in canines, the efficacy of canine PRP systems, and the clinical applications for PRP therapy in dogs. Abbreviations: PRP: Platelet rich plasma LR-PRP: Leukocyte rich platelet rich plasma LP-PRP: Leukocyte poor platelet rich plasma ACP: autologous conditioned plasma WBC: white blood cell RBC: red blood cell